2000
DOI: 10.1002/(sici)1097-4652(200006)183:3<355::aid-jcp8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced inhibition of ?-methyl-D-glucopyranoside uptake is mediated by protein kinase C-dependent activation of arachidonic acid release in primary cultured rabbit renal proximal tubule cells

Abstract: Abnormal glucose handling in the proximal tubule may play an important role in the development of diabetic nephropathy. Thus, the present study was designed to examine the effect of high glucose on alpha-methyl-D-glucopyranoside (alpha-MG) uptake and its signaling pathways in the primary cultured rabbit renal proximal tubule cells (PTCs). When PTCs were preincubated with 25 or 50 mM glucose for 4 h, 25 or 50 mM glucose significantly inhibited alpha-MG uptake, while 25 or 50 mM mannitol and L-glucose did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…33). Recent reports including our works suggest that the activity of SGLT is related to the development of diabetic nephropathy (15,16,29). ANG II also has been reported to be involved in the onset of diabetic nephropathy (5).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…33). Recent reports including our works suggest that the activity of SGLT is related to the development of diabetic nephropathy (15,16,29). ANG II also has been reported to be involved in the onset of diabetic nephropathy (5).…”
mentioning
confidence: 68%
“…32), and 3) the concentration of ANG II is increased in diabetic animals (46). Recently, we have demonstrated that high glucose inhibited ␣-MG uptake in PTCs (15,16). Others have demonstrated that high glucose resulted in a reduction of the expression and activity of SGLTs (23) and that SGLT activity was decreased in brushborder membrane vesicles of diabetic rats (19).…”
Section: Discussionmentioning
confidence: 98%
“…These multiple isotypes of PKC have variable tissue distributions, biochemical regulations, and physiological functions that at times are cell specific. Many of them, including, ␣, ␤, ␦, ε, and , have been reported to modulate hyperglycemia-induced renal injury, consequentially leading to fibrosis (21,61). In addition, it has been shown that the activity of PKC parallels that of TGF-␤ and fibronectin protein expression, which can be blocked by inhibition of PKC (19,52).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that high glucose inhibits the activity of SGLT by increasing the AA release, which is regulated by PKC-oxidative stress (Figure 2). 67 Therefore, the PKC-induced activation of PLA 2 provides a novel mechanism that directly implicates hyperglycemia in the inhibition of the glucose reabsorption of PTCs. This abnormal glucose handling in the proximal tubule might play an important role in the development of diabetic nephropathy, even though renal PTCs do not appear to be primary targets for diabetic injury.…”
Section: High Glucose and Sgltsmentioning
confidence: 99%
“…74 Therefore, ANG II is involved in the high glucoseinduced inhibition of a-MG uptake through an increase in ANG II by high glucose levels. 67,71,98 Mice overexpressing a dominant-negative isoform of the EGFR were protected from renal lesions such as glomerulosclerosis, tubular atrophy, fibrosis, mononuclear cell infiltration during chronic ANG II infusion, suggesting that EGFR plays a key role in ANG II-dependent EGFR transactivation in renal pathogenesis. 99 Many of the deleterious effects of ANG II in the cardiovascular system are mediated through the matrix metalloproteinase-dependent activation of the EGFR.…”
mentioning
confidence: 99%